2014
DOI: 10.1061/(asce)st.1943-541x.0000939
|View full text |Cite
|
Sign up to set email alerts
|

Application of Reliability-Based Robustness Assessment of Steel Moment Resisting Frame Structures under Post-Mainshock Cascading Events

Abstract: This paper proposes a reliability-based framework for quantifying structural robustness considering the occurrence of a major earthquake (mainshock) and subsequent cascading hazard events, such as aftershocks that are triggered by the mainshock. These events can significantly increase the probability of failure of buildings, especially for structures that are damaged during the mainshock. The application of the proposed framework is exemplified through three numerical case studies. The case studies correspond … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 36 publications
2
18
0
Order By: Relevance
“…Two‐dimensional centerline nonlinear finite element models of a N‐S external frame of each of the three buildings are developed in OpenSees and used for the structural analysis. Similar to the approach followed by Ribeiro et al , and Barbosa et al , , strong‐column weak‐beam ductile behavior is assumed for all structures. Brittle mechanisms and connection fracture modes are not considered.…”
Section: Building Modelsmentioning
confidence: 99%
“…Two‐dimensional centerline nonlinear finite element models of a N‐S external frame of each of the three buildings are developed in OpenSees and used for the structural analysis. Similar to the approach followed by Ribeiro et al , and Barbosa et al , , strong‐column weak‐beam ductile behavior is assumed for all structures. Brittle mechanisms and connection fracture modes are not considered.…”
Section: Building Modelsmentioning
confidence: 99%
“…This indicates the SMRF with low damages from the mainshock experiences somewhat small reductions in its collapse capacity during future earthquakes, while the effect of aftershocks on the collapse capacity becomes more pronounced when the structural damage during the mainshock increases. Similar observations for the steel frame buildings were reported in previous studies Ribeiro et al 2014). Figure 7-6 Median IDA curves at three damage states for SMRF and SVD frame under seismic sequences…”
Section: Mainshock Seismic Assessmentsupporting
confidence: 80%
“…Residual story drifts are calculated by continuing the analyses for at least 20 seconds after the end of the seismic event. As previous probability based studies suggested 10% inter-story drift ratio is considered to define the collapse in numerical simulations (Ribeiro et al, 2014).…”
Section: Performance Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Past earthquakes have demonstrated catastrophic structural failure of mainshock-damaged structures subjected to cascading events, defined as events likely to be triggered by the main earthquake, such as aftershocks, explosions and tsunamis (Li et al 2014;Ribeiro et al 2014). This study is focused on multiple earthquakes consisting of the mainshock (MS) and aftershocks.…”
Section: Introductionmentioning
confidence: 99%